2018
DOI: 10.2166/ws.2018.051
|View full text |Cite
|
Sign up to set email alerts
|

Frequency analysis of low flows in intermittent and non-intermittent rivers from hydrological basins in Turkey

Abstract: This study attempts to find out the best-fit probability distribution function to low flows using the up-to-date data of intermittent and non-intermittent rivers in four hydrological basins from different regions in Turkey. Frequency analysis of D = 1-, 7-, 14-, 30-, 90- and 273-day low flows calculated from the daily flow time series of each stream gauge was performed. Weibull (W2), Gamma (G2), Generalized Extreme Value (GEV) and Log-Normal (LN2) are selected among the 2-parameter probability distribution fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 18 publications
0
21
0
3
Order By: Relevance
“…Agwata [76] used an L-moments statistics approach to assess probability distributions in the Upper Tana Basin, and found that Pearson type 3 is not the best-fit model in the area, which is also reflected in this study. Elsewhere in the world, Eris, Aksoy [77] showed that the lognormal and Weibull distribution functions mostly conform to low flows in hydrological basins in Turkey [5]. Furthermore, using the maximum likelihood approach, Eris selected the Weibull function as the best probability distribution function suitable for the analysis of eight sites in the Niger Basin.…”
Section: Discussionmentioning
confidence: 99%
“…Agwata [76] used an L-moments statistics approach to assess probability distributions in the Upper Tana Basin, and found that Pearson type 3 is not the best-fit model in the area, which is also reflected in this study. Elsewhere in the world, Eris, Aksoy [77] showed that the lognormal and Weibull distribution functions mostly conform to low flows in hydrological basins in Turkey [5]. Furthermore, using the maximum likelihood approach, Eris selected the Weibull function as the best probability distribution function suitable for the analysis of eight sites in the Niger Basin.…”
Section: Discussionmentioning
confidence: 99%
“…Models have to capture discontinuities in the flow regime during a substantial period of the year (Smith et al, 2010;Pumo et al, 2014;Gong et al, 2014;Eris et al, 2018). Models have to capture discontinuities in the flow regime during a substantial period of the year (Smith et al, 2010;Pumo et al, 2014;Gong et al, 2014;Eris et al, 2018).…”
mentioning
confidence: 99%
“…From a modelling perspective, simulation of intermittent catchments' response to rainfall is a challenging endeavour. Models have to capture discontinuities in the flow regime during a substantial period of the year (Smith et al, 2010;Pumo et al, 2014;Gong et al, 2014;Eris et al, 2018). Additionally, because streamflow is not continuous, a full picture of the catchment water balance is required, such that modelling groundwater storage changes becomes important for water management.…”
mentioning
confidence: 99%
“…The basin is located between the north latitudes 36 • 33 to 38 • 44 , and the east longitudes 35 • 15 to 37 • 43 [39]. Mountains in the basin are as high as 2500 m [40]. The southern part of the basin stays in the Cukurova Plain, which is one of the most important agricultural production areas in Turkey [41].…”
Section: Study Area and Datamentioning
confidence: 99%